Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

how do you solve 9c(c-11)+10(5c-3)=3c(c+5)+c(6c-3)-30 if we are multiplying polynomials by monomials

Sagot :

[tex]9c(c-11)+10(5c-3)=3c(c+5)+c(6c-3)-30\\\\9c(c)+9c(-11)+10(5c)+10(-3)=3c(c)+3c(5)+c(6c)+c(-3)-30\\\\9c^2-99c+50c-30=3c^2+15c+6c^2-3c-30\\\\9c^2-49c-30=9c^2+12c-30\ \ \ |subtract\ (9c^2-30)\ from\ both\ sides\\\\-49c=12c\ \ \ \ |subtract\ 12c\ from\ both\ sides\\\\-61c=0\ \ \ \ |divide\ both\ sides\ by\ (-61)\\\\\boxed{c=0}[/tex]